(untitled) (Global Journal of Human-Social Science, 2022)
The growth of urbanization has reduced the availability of green spaces GS and the decrease in these spaces as well as the difficulty in accessing them has impacts on human physical and mental health proven by research that deeply investigates this theme around the world Thus understanding the impacts of GS on human perception within the contemporary scenario is of fundamental importance since the population has been subjected to a high level of stress generated by the high work demand as well as the quarantine scenario imposed by the Covid-19 pandemic Based on this the present research aimed to investigate the implications of GS on self-reported well-being through the perceptions generated by these environments and for that a systematic literature review 2010-2020 was carried out based on selected pre-criteria which were analyzed qualitatively and quantitatively through meta-analysis The results describe and discuss 14 implications of GS for human well-being and mental health 7 demographic differences verified in the way of perceiving these environments and statistical dependencies in the research pattern of certain study variables in the last decade Thus an unprecedented compilation of implications and perceptive differences caused by GS is presented serving as a theoretical contribution to the government planners architects and urbanists in the provision of cities with potential to mitigate stress and favorable to human well-being